AgriTech4Kenya innovation challenge 2024: Consultation workshop report - CGIAR Accelerate for Impact Platform (2024)
The AgriTech4Kenya Innovation Challenge 2024 is driving Kenya’s agrifood systems transformation by facilitating the development, deployment, adoption, and scaling of high-impact science-based agritech solutions tailored to the needs of the nation’s smallholder farmers and value chain stakeholders. The project’s Consultation Workshop held in Nairobi in April 2024 catalyzed dialogue among key players from within Kenya’s agri-food sector, including government officials, academicians, researchers, incubators, accelerators, venture funds, startups, and farmers.